2015
DOI: 10.1111/jace.13592
|View full text |Cite
|
Sign up to set email alerts
|

Er3+ Ions‐Doped Germano‐Gallate Oxyfluoride Glass‐Ceramics Containing BaF2 Nanocrystals

Abstract: Er3+ ions‐doped germano‐gallate oxyfluoride glass‐ceramic containing BaF2 nanocrystals was prepared through conventional melt quenching and subsequent thermal treatment method. X‐ray diffraction patterns and transmission electron microscope images confirmed the formation of BaF2 nanocrystals in glass‐ceramics. Preferential incorporation of Er3+ ions into the BaF2 nanocrystals were confirmed by the absorption spectra and emission spectra, and enhanced upconversion emission and infrared emission were observed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In the research, it may be found that rare-earth ions like Er 3+ are the luminescence centers in BaF 2 nanocrystals in the glass-ceramic [101,134,135,136]. Chen et al obtained transparent glass-ceramics containing BaF 2 nanocrystals doped with Er 3+ , prepared by the sol-gel route.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research, it may be found that rare-earth ions like Er 3+ are the luminescence centers in BaF 2 nanocrystals in the glass-ceramic [101,134,135,136]. Chen et al obtained transparent glass-ceramics containing BaF 2 nanocrystals doped with Er 3+ , prepared by the sol-gel route.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced upconversion luminescence of the Er 3+ ions in transparent oxyfluoride GCs containing BaF 2 nanocrystals in the SiO 2 -ZnF 2 -BaF 2 -ErF 3 system has been also investigated by Qiao et al [135]. The erbium-doped germano-gallate oxyfluoride glass-ceramics containing BaF 2 nanocrystals with the high transmittance in the mid-infrared region were prepared by Zhao et al [136]. Unfortunately, to the best of our knowledge, no reports of the transparent Er 3+ -doped BaF 2 glass-ceramic in the oxyfluoride phospho-tellurite exist in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, lanthanide (Ln 3+ ) and transition metal (TM) ions doped glass‐ceramics (GC) have gained much importance in the field of optical thermometric study . The Ln 3+ ‐doped based optical thermometers are primarily based on temperature correlated fluorescence intensity ratio (FIR) of thermally coupled energy levels, such as 2 H 11/2 and 4 S 3/2 of Er 3+ ions .…”
Section: Introductionmentioning
confidence: 99%
“…Rare‐earth ‐doped oxyfluoride glasses have attracted much attention for their potential applications in photonic devices due to their interesting optical properties . In particular, inorganic heavy‐metal glasses play an important role, due to their features, such as high refractive index, density, and low phonon energies .…”
Section: Introductionmentioning
confidence: 99%